2023
DOI: 10.1111/ejn.15935
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure of diabetes and progestin‐mediated autistic biomarker in peripheral blood mononuclear cells

Abstract: Despite the importance of early diagnosis and intervention, the diagnosis of autism spectrum disorders (ASDs) remains delayed as it is mostly based on clinical symptoms and abnormal behaviours appearing after 2 years of age. Identification of autistic markers remains a top priority in achieving an early and effective ASD diagnosis. We have previously reported that prenatal exposure of hormones or diabetes triggers epigenetic changes and oxidative stress, resulting in gene suppression with autism-like behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(79 reference statements)
1
0
0
Order By: Relevance
“…This suggests that diabetes may contribute to the downregulation of GPER. Consistent with our findings, a recent study reported the suppression of GPER mRNA expression in the brain and peripheral blood mononuclear cells of the offspring of streptozotocin-induced diabetic mice [22]. According to Jiao et al 2023, downregulation can result from inherited epigenetic modifications induced by diabetes [22].…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that diabetes may contribute to the downregulation of GPER. Consistent with our findings, a recent study reported the suppression of GPER mRNA expression in the brain and peripheral blood mononuclear cells of the offspring of streptozotocin-induced diabetic mice [22]. According to Jiao et al 2023, downregulation can result from inherited epigenetic modifications induced by diabetes [22].…”
Section: Discussionsupporting
confidence: 92%
“…In particular, EVs carried increased concentrations of neurotensin, which has been shown to increase IL-1β, a cytokine associated with ASD 72 , 73 . Peripheral blood mononuclear cells from patients with ASD were found to have lower levels of mRNAs coding for estrogen receptors, estrogen-related receptors, and retinoic acid-related receptors 74 . These findings support previous associations between high levels of estrogen in the prenatal window and ASD pathogenesis 75 .…”
Section: Mrna Cargoes As Biomarkers Of Diseasementioning
confidence: 99%